2021
DOI: 10.3389/fmicb.2021.681983
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity and Metabolite Profile of Fermenting Millet in the Production of Hausa koko, a Ghanaian Fermented Cereal Porridge

Abstract: Hausa koko is an indigenous porridge processed from millet in Ghana. The process involves fermentation stages, giving the characteristic organoleptic properties of the product that is produced largely at a small-scale household level and sold as a street food. Like many other indigenous foods, quality control is problematic and depends on the skills of the processor. In order to improve the quality of the product and standardize the process for large-scale production, we need a deeper understanding of the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…16 Antony et al, 35 showed that natural fermentation of FM increased the LAB count significantly during the first 24 h of fermentation. A more recent study by Atter et al, 36 also highlighted that in Hausa koko (a fermented millet-based porridge) LAB count increased during the first 12-24 h fermentation. LAB may contribute to the formation of lactic acid while yeast may produce succinic acid resulting in acidification of the starch slurry.…”
Section: Resultsmentioning
confidence: 92%
“…16 Antony et al, 35 showed that natural fermentation of FM increased the LAB count significantly during the first 24 h of fermentation. A more recent study by Atter et al, 36 also highlighted that in Hausa koko (a fermented millet-based porridge) LAB count increased during the first 12-24 h fermentation. LAB may contribute to the formation of lactic acid while yeast may produce succinic acid resulting in acidification of the starch slurry.…”
Section: Resultsmentioning
confidence: 92%
“…However, following food fermentation, ffs can still contain significant concentration of mycotoxins, particularly when the raw material or substrate is highly contaminated. Moreover, some fermentation processes provide favorable conditions for the growth and production of mycotoxins by toxigenic fungal species of Aspergillus , Fusarium and Penicillium genera 102 , 103 . In addition, fermentation conditions such as low pH, facilitate the hydrolysis of conjugated mycotoxins (such as deoxynivalenol-3-glucoside and zearalenone-16-glucoside) back to their precursor mycotoxins, which ultimately, result in the accumulation of mycotoxins.…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…This species has also been isolated from plants such as agave [ 18 ]; fruits such as overripened mango pulp [ 19 ]; vegetables such as rotting onions [ 20 ]; and agro-industrial residues in sugar mills [ 21 ], sugarcane bagasse hydrolysates [ 22 ], blue agave bagasse [ 23 ], coffee wet processing wastewater [ 24 ], and distillery effluents and molasses [ 25 ]. K. marxianus is also part of the microbiota involved in the fermentation of cereal-based African fermented beverages [ 26 ], French cider [ 27 ], Georgian wine [ 28 ], Brazilian cachaça [ 29 ], and Mexican agave-based spirits tequila and mezcal [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%